2022
DOI: 10.3389/fmicb.2022.1050247
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Lactobacillus with prebiotics on KPC-2-producing Klebsiella pneumoniae

Abstract: ObjectivesThis study investigated the inhibitory effect of Lactobacillus spp. with prebiotics against Klebsiella pneumoniae carbapenemase-2 (KPC-2)-producing Klebsiella pneumoniae using both in vitro experiments and animal models.MethodsThirty-three Lactobacillus spp. strains were confirmed by 16S rDNA sequencing, and four different PFGE genotyped KPC-2-producing K. pneumoniae strains were selected for investigation. In vitro studies, including broth microdilution assays, changes in pH values in lactobacilli c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Recent studies have reported that the anticolonization of K. pneumoniae by Lactobacillus spp. was attributed to increased acetic acid and regulation in microbiota in mice intestinal [ 29 , 34 ]. To investigate the mechanism underlying the inhibition of CR-hvKP colonization by Lactobacillus spp., we repeated the K. pneumoniae colonization experiment and replaced Lactobacillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported that the anticolonization of K. pneumoniae by Lactobacillus spp. was attributed to increased acetic acid and regulation in microbiota in mice intestinal [ 29 , 34 ]. To investigate the mechanism underlying the inhibition of CR-hvKP colonization by Lactobacillus spp., we repeated the K. pneumoniae colonization experiment and replaced Lactobacillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…They play a significant role in maintaining the homeostasis of this environment and the disturbance of which could affect the development of many uropathogens 15 , 39 . Many recent studies focus on the antibacterial and antibiofilm properties of natural microbiota of the urinary tract against the most common UTI pathogens such as: Escherichia coli, which cause approximately 80% of UTIs 40 , 41 , Proteus mirabilis 14 , 42 or Klebsiella pneumoniae 43 , 44 . Additionally, a lot of scientific works concentrate on the practical use of selected Lactobacillus strains to UTIs treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Klebsiella could disrupt the gut barrier (Nakamoto et al, 2019), which not only trigger a systemic or local inflammatory response that further altering the overall immune homeostasis of the host to exacerbate the occurrence of inflammatory lung injury (Belkaid & Hand, 2014), but also lead to a risk factor for pneumonia-induced lung injury (Liu et al, 2018). Lactobacillus, a genus of beneficial bacteria, can inhibit the growth and activity of Klebsiella (Tang et al, 2022). As a potential prebiotic-like polysaccharide, POP might promote the growth of Lactobacillus to inhibit the growth and activity of Klebsiella.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota was modulated by a short‐term (3‐day) POP pre‐intervention and the trend was sustained of Lactobacillus in the donor mice, which played important roles in gut microbiota for prevention in LPS‐induced injury. Lactobacillus , a genus of beneficial bacteria, can inhibit the growth and activity of Klebsiella (Tang et al, 2022 ). As a potential prebiotic‐like polysaccharide, POP might promote the growth of Lactobacillus to inhibit the growth and activity of Klebsiella .…”
Section: Discussionmentioning
confidence: 99%